2017
DOI: 10.1016/j.resp.2017.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem mechanisms underlying the cough reflex and its regulation

Abstract: A B S T R A C TCough is a very important airway protective reflex. Cough-related inputs are conveyed to the caudal nucleus tractus solitarii (cNTS) that projects to the brainstem respiratory network. The latter is reconfigured to generate the cough motor pattern. A high degree of modulation is exerted on second-order neurons and the brainstem respiratory network by sensory inputs and higher brain areas. Two medullary structures proved to have key functions in cough production and to be strategic sites of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 218 publications
(348 reference statements)
2
31
0
Order By: Relevance
“…2 and 3) and these results are consistent with previous findings (Poliacek et al, 2017a,b; Mutolo, 2017; Mutolo et al, 2008; Cinelli et al, 2016). Present findings support the concept that neuronal structures of the rNTS are involved in the control of the cough reflex.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2 and 3) and these results are consistent with previous findings (Poliacek et al, 2017a,b; Mutolo, 2017; Mutolo et al, 2008; Cinelli et al, 2016). Present findings support the concept that neuronal structures of the rNTS are involved in the control of the cough reflex.…”
Section: Discussionsupporting
confidence: 93%
“…The multiplicity of neuronal phenotypes and responses to perturbation of NTS neurons (Lipski et al, 1991; Paton, 1998; Paton et al, 1999) reveals a complex role for the NTS in regulation of cough excitability, its sequencing, motor drive and the spatiotemporal control of cough motor pattern (Poliacek et al, 2017a,b). Mutolo et al (2007, 2009), Mutolo (2017), Cinelli et al (2016) have repeatedly shown in the rabbit that pharmacological perturbation of the NTS can alter the duration of the inspiratory and expiratory phases of coughing, which is strong evidence for a role of this medullary area in cough rhythmogenesis.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Cough is one of the most important defensive reflex brought into action by actually or potentially damaging events applied to the airways (Korpáš and Tomori, 1979). Peripheral and central mechanisms underlying nociception and cough share similar features; neuroactive agents involved in the central control of pain sensation (Millan, 2002;Yan et al, 2017) and concomitant reflex responses play a role also in the downregulation of the cough reflex (see Mutolo, 2017 also for further Refs. Mutolo et al, 2008Mutolo et al, , 2012Mutolo et al, , 2014Cinelli et al, 2013Cinelli et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Several brainstem areas appear to contribute to the generation and regulation of cough responses in mammals (e.g. Gestreau et al, 1997;Bongianni et al, 1998;Jakus et al, 2008;Mutolo et al, 2002b;Poliacek et al, 2004Poliacek et al, , 2005Poliacek et al, , 2014Shannon et al, 2004;Simera et al, 2013; see also Mutolo, 2017). Recent findings obtained mainly in the rabbit (for review see Mutolo, 2017) have led to the proposal that two medullary structures play a prominent role in the control of cough reflex responses and are sites of action of antitussive or protussive drugs, i.e.…”
Section: Introductionmentioning
confidence: 99%